ETHNIC AND CULTURAL CHALLENGES IN FOREIGN LANGUAGE EDUCATION: SPEECH ETIQUETTE - Borisovna Kurilenko, Victoria; Biryukova, Yulia Nickolaevna (Revista Inclusiones, 2021)
The article is aimed to determine the specifics of the linguistic and communicative expression of the etiquette category both in Russian and foreign linguoculture in relation to academic communication. Russian and foreign cultures share common features and differences in order to further develop a methodology for teaching Russian as a foreign language in a multicultural audience. As the analysis of foreign and Russian languages shows the common features are the way both nationalists address their interlocutors, the elderly people and children. The differences are such features as the importance of the degree of kinship between people, forms of address to strangers, easy rules of Russian etiquette and the complexity of the rules of a foreign etiquette, forms of address to colleagues at work. At the end of the article the methodological application in teaching the foreign languages is provided. The authors of the article suggest to provide different modern technologies to teach a foreign language taking into consideration the ethnic specifics of a language.